ANALISIS TREN PUBLIKASI DAN HUBUNGAN ANTARA UKURAN PERUSAHAAN DENGAN NILAI PERUSAHAAN: PENDEKATAN BIBLIOMETRIK - Dermawan, Wildan Dwi; Pradani, Tiara (AKUNTANSI DEWANTARA, 2025)
The aim of this study is to explore publication trends and the relationship between firm size and firm value and provide recommendations for researchers. The database used is dimensions.ai from 1990 - 2024. The data collected were 482 documents using the keywords "firm size AND firm value" from the types of articles and proceedings documents. This study uses R Studio software to analyse and map the data comprehensively. In general, it was found that the increasing trend is consistent when viewed from the development of research every year. The most relevant journal source is SSRN Electronic Journal, while the most productive author and country is Tony Sudigro from Indonesia. However, the authors who have the most impact on this research are Alexandre Di Miceli da Silveira and Lucas Ayres B. de C. Barros. Next, the latest topics that are often discussed in this research are information asymmetry, stock exchange and corporate governance. In addition, this study also found that there is a relationship between firm size and firm value.